The impact of harvest length and detachment of the interosseous membrane on donor-site morbidity following free fibula flap surgery—a biomechanical experimental study. Issue 11 (November 2018) - Hakim, Samer George; Tehrany, Ali Shakery; Wendlandt, Robert; Jacobsen, Hans-Christian; Trenkle, Thomas; Sieg, Peter
Abstract: Purpose: The fibula flap has been established for orofacial reconstruction following ablative surgery. Donor-site morbidity of the lower leg may be explained by the harvest technique and particularly by detachment of the M. extensor halluces longus (EHL) and M. extensor digitorum longus (EDL). Material and methods: On cadaveric lower leg specimens, the tendons of the EHL and EDL were dissected at the proximal phalanges and loaded with corresponding weights. The average displacement of the muscle was evaluated during the harvesting procedure. Results: Cumulative detachment of the interosseous membrane caused considerable displacement of the EHL but less impairment of the EDL. Segmental and cumulative osteotomy of the fibula implicated significant displacement of both EHL and EDL. Conclusion: A recommendation can be given for cautious selection of osteotomy site of the fibula and for limited sacrifice of the fibula and adjacent attachments of the extensors to keep local-site morbidity at a minimum.